PROFILE OF KNEE OSTEOARTHRITIS PATIENTS IN THE DEPARTMENT OF PHYSICAL MEDICINE AND REHABILITATION, MOHAMMAD HOESIN HOSPITAL, PALEMBANG - Rara Intan Rahmawati; Jalalin; Septadina, Indri Seta; Dwiwulandari, Margareta Dewi; Fatimah, Nyimas (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Osteoarthritis (OA) is a common disease . degenerative musculoskeletal disease , especially between That elderly . Osteoarthritis of the knee is That most common form And is marked by pain , stiffness , and limited range from movement , leading to decrease physique function And quality from This life​ descriptive cross-sectional study aims to describe That characteristics from knee OA patients at Mohammad Hoesin Regional Hospital , Palembang, including sociodemographic factors , BMI, clinical manifestation , duration diagnosis , comorbidities , treatment , and Compliance . Data obtained . from Be patient interview And medical notes And analyzed using SPSS version 26. Most of the Patients were mostly female (88.5%), had normal BMI (61.5%), and mild symptoms. pain (69.2%), bilateral involvement (73.1%), mild OA value (76.9%), and currently functional ability (46.2%) . The majority have diagnosed For Again compared to One years (92.3%), with NO history trauma (61.5%) or comorbidities (69.2%). TENS and the exercise is most often managed therapy , with Again compared to two treatment modality provided (100.0%) and use of NSAIDs reported in 30.4% of patients . Most of them not using ongoing assistance (96.4%) and did not undergo TKR (96.4%). Treatment obedience is very good , with all patient attend therapy 2–3 times per week . In conclusion , knee OA patients on this hospital is mostly Woman with mild bilateral disease And Good treatment compliance .